The Validity of Different F Wave Parameters in The Diagnosis of Diabetic Axonal Polyneuropathy (Iraqi Journal of Medical Sciences, 2020)
Background: The underlying pathology of the vast majority of diabetic polyneuropathies is axonal degeneration. F wave study is one of the most sensitive indices of the severity of neuropathy. Objective: To test the validity of different F wave parameters including F minimum latency, F wave index and F Jitter in the diagnosis of diabetic axonal peripheral neuropathy.Methods: Eighty type 2 diabetics aged 52.57±5.62 years with disease duration of 1 to 18 years and 90 aged-matched healthy volunteers serve as the control group. Both groups were submitted to medical history, clinical neurological examination, and electrophysiological tests of both upper and lower limbs.Results: Tibial and ulnar F wave latencies were significantly prolonged in diabetic patients (p < 0.001). Tibial F index for male patients shows significantly lower value as compared to the control group. Ulnar F wave latency was 76.7% sensitive and 89.3% specific in female patients while tibial F wave latency was 80% sensitive and 81.3% specific in male patients.Conclusion: F wave is a precise parameter in detecting diabetic axonal peripheral neuropathy. Minimal F-wave latency is more sensitive than both F index and F Jitter in the diagnosis of axonal neuropathy in diabetic patients.Keywords: DM, Axonal neuropathy, Ulnar, Tibial, F-wave latency, F-jitter, F-indexCitation: Yaqoub ZA, Kaddor HG, Hamdan FB. The validity of different F wave parameters in the diagnosis of diabetic axonal polyneuropathy. Iraqi JMS. 2020; 18(1): 29-38. doi: 10.22578/IJMS.18.1.5
Keywords: DM; Axonal neuropathy; Ulnar; Tibial; Fwave latency; Fjitter; Findex